Strengthening the Marketing Capacity of Water Hyacinth Compost Products Through Branding and Packaging Training in the Cempaka Women Farmers Group in Langung Village, West Aceh - Khairun Nisa; Liston Siringo Ringo; Abdul Muzammil (Pascasarjana Universitas Mataram, 2026)
The Cempaka Women's Farmers Group (KWT Cempaka) in Langung Village, Meurebo District, West Aceh Regency, has used water hyacinth as raw material for making organic compost which has quite large economic and environmental potential. However, compost products still face challenges in marketing, especially regarding product identity, packaging design and branding strategies that have not been developed optimally. This community service program aims to increase the marketing capacity of water hyacinth compost products through branding and product packaging training. The methods used include education, participatory training, logo design workshops, assistance with product label design, and the introduction of attractive and informative packaging techniques. This program was implemented with KWT Cempaka members as the main participants. The results show an increase in participants' understanding of the importance of branding in product marketing, increased ability to develop brand identity, and the creation of more attractive logo and packaging designs with higher market value. Through this program, the water hyacinth compost products produced by KWT Cempaka have the opportunity for greater market acceptance and increased competitiveness, thus supporting the sustainable development of group business activities. However, at this stage KWT. Cempaka is still marketing it in simple rice jute packaging and in the future it will use more attractive packaging.